Effective Decolorization of Poly-γ-Glutamic Acid Fermentation Broth by Integrated Activated Carbon Adsorption and Isoelectric Point Precipitation of Glutamic Acid - Xiusheng Si; Jicheng Li; Tingbin Zhao; Weifeng Cao; Changsheng Qiao (Molecules)
Poly-γ-glutamic acid (γ-PGA) is widely used in the field of biomedicine, food, agriculture, and ecological remediation. For the biosynthesis of γ-PGA, the pigments and remaining glutamate are two big problems that impede γ-PGA production by fermentation, and a trade-off between the decolorization rate and γ-PGA recovery rate during the purification process was found. The optimized static activated carbon adsorption conditions for treating the 2-times diluted cell-free supernatant (i.e., feed solution) was as follows: 0.51% 200-mesh, 1000 iodine value, coal-based activated carbon, pH 6.0, 140 min, and 40 °C. Under the optimized conditions, the decolorization rate reached 94.42%, and the recovery rate of γ-PGA was 94.22%. During the adsorption process, the pigments were adsorbed on the activated carbon surface in a monolayer, and the process was a spontaneous, heat-absorbing, and entropy-increasing process. Then, the decolorization flow rate optimized for the dynamic decolorization experiment was 1 BV/h. However, the remaining glutamate was still a problem after the activated carbon adsorption. After isoelectric point (IEP) precipitation of glutamic acid, the glutamic acid can be recovered, and the residual pigment can be further removed. Finally, an integrated decolorization process of activated carbon adsorption and IEP precipitation of glutamic acid was developed. After the integrated process, the decolorization and glutamic acid precipitation rates were 95.80% and 49.02%, respectively. The recovered glutamic acid can be reused in the next fermentation process.